Evaluating the Prevalence and Distribution of Quasi-formal Employment in Europe - Williams, Colin; Padmore, Jo (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2013)
SummaryTo show how formal and informal jobs are not always discrete, this paper uncovers how many formal employees in the European Union are paid two wages by their formal employers, an official declared salary and an additional undeclared wage, thus allowing employers to evade their full social insurance and tax liabilities. Analyzing a 2007 Eurobarometer survey involving 26,659 face-to-face interviews in the 27 member states of the European Union (EU-27), one in 18 formal employees are found to engage in such quasi-formal employment, receiving on average one-quarter of their gross salary on an undeclared basis. Multi-level logistic regression analysis reveals that quasi-formal employment is significantly more prevalent in East-Central Europe, in smaller businesses and the construction sector, and amongst men, younger persons and the lower paid. The dichotomous depiction of employment as either formal or informal therefore needs to be transcended and a finer-grained continuum of types of employment depicted from wholly formal to wholly informal with many varieties in-between. The paper then briefly reviews what might be done to tackle this illegitimate wage practice. This clearly displays that this quasi-formal form of employment needs to be more fully integrated into discussions when discussing how to tackle undeclared work, since some measures that tackle wholly undeclared work, such as reducing the minimum wage, might simply allow formal employers to pay a larger portion of their formal employees’ earnings as an additional undeclared wage, rather than facilitate the creation of fully formal employment.